Analysis of Perceived Value and Price Perception on Repurchase Intention with Word of Mouth Electronic Information as a Mediating Variable - Rahmadhani, Aqiela; Ramdan, Asep Muhamad; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the effect of perceived value and perceived price on repurchase intention through electronic word of mouth as a mediating variable for consumers of Solaria fast food restaurants in Sukabumi. The background of this study includes the rapid development of the culinary industry in Indonesia, especially fast food restaurants, as well as factors that influence consumer repurchase intentions. The research method used is a quantitative approach with a causal descriptive design. Data were collected through questionnaires distributed to 185 respondents of Solaria consumers in Sukabumi. The data analysis technique used was Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that perceived value and perceived price have a positive and significant influence on repurchase intention. Electronic word of mouth was also shown to have a significant mediating influence between perceived value and price perception on repurchase intentions. This study concludes that to increase repurchase intentions, fast food restaurants such as Solaria need to increase perceived value and positive price perceptions in the eyes of consumers, and utilize electronic word of mouth as an effective marketing tool.